Multivariate analysis of prognostic factors in patients with lung cancer - Liu, Changjiang; Ma, Minting; Zhou, Xuetao; Zhang, Zefeng; Guo, Yang (Frontiers in Oncology, 2023)
Objective: Lung cancer is the leading cause of cancer-related mortality in China. The purpose of this study was to determine the effect of non-therapeutic and therapeutic factors of patients with lung cancer on survival rate. Methods: In this retrospective study, a total of 458 patients diagnosed as lung cancer at the Department of Thoracic Surgery, the Fourth Affiliated Hospital of Hebei Medical University from September 2008 to October 2013 were enrolled. The COX proportional hazards model was used to analyze the possible factors affecting the survival of patients. Model variables included age, sex, family history, smoking, tumor location, pathological type, stage, chemotherapy, radiotherapy, operation, and targeted therapy. Results: The median survival time (MST) was 32.0 months (95% CI: 29.0-34.0 months), while the 1-, 3-, and 5-year survival rates were 70.74%, 36.90%, and 30.13%, respectively. The univariate analysis showed that stage, chemotherapy, radiotherapy, and operation significantly affected the median survival time of patients. Multivariate cox regression analysis suggested that sex (female vs male, 2.096, 95% CI: 1.606-2.736), stage (stage I vs IV, 0.111, 95% CI: 0.039-0.314; stage II vs IV, 0.218, 95%CI: 0.089-0.535), chemotherapy (no vs yes, 0.469, 95% CI: 0.297-0.742), and operation (no vs yes, 2.667, 95% CI: 1.174-6.055) were independently associated with the survival of patients with lung cancer. Conclusion: Our study showed that male, early stage, operation were protective factors for the survival of patients, while female, advanced stage, chemotherapy were risk factors for the survival of patients. Larger studies are required to address the usefulness of these prognostic factors in defining the management of patients with lung cancer.